Pulmonary MALToma Synchronous with Metastatic Prostate Adenocarcinoma: A Diagnostic Challenge - Aaron Braddy; Rahul Janardan Mogal; Anthony John Maddox; Andrew Bryan Timothy Barlow (European Journal of Case Reports in Internal Medicine, 2020)
Objectives: We describe the novel case of a patient presenting with pulmonary mucosa-associated lymphoid tissue lymphoma (pMALToma) synchronous with metastatic prostate adenocarcinoma. Materials and methods: We report the clinical, laboratory, radiological and histological findings of the above patient. Results: While the patient’s metastatic prostate adenocarcinoma responded well to chemo-radio-hormonal therapy, a persistent area of lung consolidation was noted and further investigated, leading to the diagnosis of concurrent pMALToma. Conclusion: It is important to pursue further investigation when there appears to be persistent change or altered disease response in malignancy if there is evidence for disease response elsewhere, as there may be two synchronous primary cancers.